THE EFFECT OF FINGER-GRIP RELAXATION TECHNIQUE ON REDUCING ANXIETY IN PREOPERATIVE CAESAREAN SECTIO PATIENTS IN THE MIDWIFERY ROOM OF KEPAHIANG REGIONAL HOSPITAL - Yulita Elvira Silviani; Ruri Maiseptyasari; Metha Fahriani; Samantha Dwi Putri (UNIVERSITAS AIRLANGGA, 2021)
ABSTRACT Sectiocaesarea is an artificial childbirth, ie the fetus is born through an intact abdominal wall and uterine incision that is still intact with the requirement, that the uterus is intact and the fetus weighs above 500 gr.The purpose of this study was to determine the effect of hand-held relaxation techniques on anxiety reduction in caesarean sectio patients in the midwifery room of Kepahiang Regional Hospital in 2019.The design of this study used the pre-experimental method, with the One Group Pretest-Posttest design approach. The population used in this study was about 80 women giving birth with caesarean section from March to May 2019 in Kepahiang District Hospital. Samples were taken using 45 accidental sampling techniques. Data were analyzed using univariate analysis, data normality test and bivariate analysis using Wilcoxon sign rank test.The results of the study were obtained from 45 patients before hand held finger relaxation that experienced mild anxiety by 22 respondents (48.9%), moderate anxiety by 11 respondents (24.4%) and severe anxiety by 12 respondents (26.7%), after they were performed there are 10 respondents (22.2%) not hand worried, 27 respondents (60.0%) have mild anxiety and 8 respondents (17.8%) have severe anxiety, there is an influence between finger grip relaxation with pre-operative patient anxiety cesarean section.It is expected to provide input to Kepahiang Regional Hospital regarding the effect of hand-held relaxation techniques on reducing anxiety in patients with Preoperative Caesarea in the Midwifery Room of Kepahiang Regional Hospital in 2019